The Determinants of bank loan provision : A study on selected commercial banks in Malaysia / Wan Shamimi Wan Hassan - Wan Hassan, Wan Shamimi (2017)
In term of finance, loan loss provision will be used by the bank as a one of tool to mitigate the risk. It plays an important role in the banks to cover the losses that the bank will face. Banks are highly levered firms, and the nature of their leverage is unique in the sense that a substantial portion of bank debt is "demandable" and is also part of the economy's payments system. Besides, banks are the most important financial intermediaries, which results from their role as providers of payments, loans and deposits, and as producers of information. The expected study will determine the impact of bank's specific factor towards loan loss provision with focus on Malaysia banking sector. The data of the expected study will be taken from the annual report as annually of the commercial bank in Malaysia. The type of the data that will be use is panel data which consist of six commercial banks from 2010 until 2016. The commercial banks that be selected include Maybank, Ambank, Affin Bank, RHB Bank, Public Bank and Hong Leong Bank. The variables that used in this study are earnings before tax and provision (EBTP), bank size (total asset), non-performing loan (NPL), debt to equity ratio and total loan.